REPORT-PFP: a consensus from the International Patellofemoral Research Network to improve REPORTing of quantitative PatelloFemoral Pain studies. Issue 20 (14th June 2021) - Barton, Christian J; De Oliveira Silva, Danilo; Morton, Sarah; Collins, Natalie J; Rathleff, Michael Skovdal; Vicenzino, Bill; van Middelkoop, Marienke; Crossley, Kay M; Callaghan, Michael J; Selfe, James; Holden, Sinead; Lack, Simon; et al.
Abstract : Patellofemoral pain is a common and often debilitating musculoskeletal condition. Clinical translation and evidence synthesis of patellofemoral pain research are compromised by heterogenous and often inadequately reported study details. This consensus statement and associated checklist provides standards for REPORTing of quantitative PatelloFemoral Pain (REPORT-PFP) research to enhance clinical translation and evidence synthesis, and support clinician engagement with research and data collection. A three-stage Delphi process was initiated at the 2015 International Patellofemoral Research Network (iPFRN) retreat. An initial e-Delphi activity (n=24) generated topics and items, which were refined at the 2017 iPFRN retreat, and voted on prior to and following the 2019 iPFRN retreat (n=51 current and past retreat participants). Voting criteria included 'strongly recommended' (essential), 'recommended' (encouraged) and uncertain/unsure. An item was included in the checklist if ≥70% respondents voted 'recommended'. Items receiving ≥70% votes for 'strongly recommended' were labelled as such. The final REPORT-PFP checklist includes 31 items (11 strongly recommended, 20 recommended), covering (i) demographics (n=2, 4); (ii) baseline symptoms and previous treatments (n=3, 7); (iii) outcome measures (2, 4); (iv) outcomes measure description (n=1, 2); (v) clinical trial methodology (0, 3) and (vi) reporting study results (n=3, 0). The REPORT-PFP checklist is ready to be used by researchers and clinicians. Strong stakeholder engagement from clinical academics during development means consistent application by the international patellofemoral pain research community is likely. Checklist adherence will improve research accessibility for clinicians and enhance future evidence synthesis.